Combined GPS, EDM and triangulation surveys of the rapid downslope motion of the western flank of Arenal Volcano, Costa Rica - Muller, Cyril (2011)
Here we present initial conclusions of a one year-long combined geodesy campaign on Arenal Volcano, in Costa Rica (2008-2009). Our data shows evidence for an active local tectonic surrounding, and a 7cm/yr displacement field of the western flank of the volcano edifice that is in general agreement with recent INSAR studies. The study shows that a rigorous combination of simultaneous GPS, EDM (Electronic Distance Measurements) and triangulation measurements provide a time-cost effective approach to volcanic monitoring.